Self-starting Simulation of a Hypersonic Inlet with Variable Free Stream Condition - J. Wu; A. Y. Yu; Y. Y. He; J. J. Le (Journal of Applied Fluid Mechanics, 2020)
The flow structure transition of a hypersonic inlet from unstart to start during accelerating trajectory is studied by numerical simulation. The results of pressure distribution along the inlet wall, mass flow rate, total pressure recovery coefficient and aerodynamic forces simulated by the quasi-steady and unsteady two dimensional and three-dimensional quasi-steady methods are compared. Analysis indicates that the two-dimensional quasi-steady and unsteady simulations can get the consistent inlet self-starting Mach number, and unsteady simulation can capture the periodical change of aerodynamic forces while this phenomena is not found in quasi-steady simulation. Due to the consistency between the quasi-steady and unsteady in self-starting Mach number in our strategy, for the self-starting process of hypersonic inlet with variable free stream condition, three-dimensional quasi-steady method can be used to approximate the real self-starting process during the acceleration of the aircraft climb, which can greatly save the computational time and improve simulation efficiency.